Bakteri resisten merkuri pada feses pasien tumpatan amalgam di Poli Gigi Puskesmas Bahu Manado - Wardalina, Geby V. (e-Biomedik, 2016)
Abstract: Amalgam is an ingredient for filling the affected tooth caries. It is a special mixture of metals containing mercury. Mercury is a natural heavy metal that has bad impact on human health. Mercury in amalgam can be released into the oral cavity and absorbed via the digestive tract, and then excreted via urine and feces. This study aimed to obtain the bacteria which were resistant to mercury in feces. This was a descriptive explorative study. Samples were taken from the stool of three patients with amalgam fillings at Dental Clinic Primary Health Center Bahu. The three patients had used amalgam fillings at least 5 years. Samples were tested morphologically, physiologically, and biochemically at the Laboratory of Biotechnology, University of Sam Ratulangi Manado. The results showed that there were 2 genus of mercury-resistant bacteria at mercury concentration of 40 ppm, namely Bacillus sp and Escherichia coli.Keywords: Amalgam, bacteria, feces, mercuryÂ Abstrak: Amalgam merupakan bahan untuk merestorasi gigi yang terkena karies. Amalagam adalah jenis logam campur khusus yang mengandung merkuri. Merkuri merupakan logam berat alamiah yang bisa berdampak buruk bagi kesehatan manusia. Merkuri pada amalgam bisa terlepas ke kavum oris, diabsorpsi ke dalam saluran pencernaan, lalu diekskresikan melalui urine dan feses. Penelitian ini bertujuan untuk mengetahui bakteri yang resisten terhadap merkuri dalam feses pada pasien dengan tumpatan amalgam. Jenis penelitian ini ialah deskriptif eksploratif. Sampel feses diambil dari 3 pasien dengan tumpatan amalgam di Poli Gigi Puskesmas Bahu yang telah menggunakan tumpatan amalgam minimal 5 tahun kemudian diuji secara morfologik, fisiologik, dan biokimia di Laboratorium Bioteknologi FMIPA Universitas Sam Ratulangi Manado. Hasil penelitian mendapatkan 2 genus bakteri resisten merkuri yang bertahan sampai konsentrasi merkuri 40 ppm, yaitu Bacillus sp dan E. Coli Kata kunci: amalgam, bakteri, feses, merkuri